Temporary atrioventricular complete block that develops following the transcatheter closure of ventricular septal defect - Erdem, Sevcan; Kızıltaş, Alev; Küçükosmanoğlu, Osman; Özbarlas, Nazan (The Turkish Journal of Pediatrics, 2012)
Atrioventricular (AV) block is a potential risk after transcatheter closure of perimembranous ventricular septal defect (VSD) with the Amplatzer perimembranous device. We present herein a case of a 6.5-year-old female patient who developed complete AV block six days after closure of VSD and recovered with steroid and salicylate treatment. It is important to be alert to the development of AV block after transcatheter perimembranous VSD closure. Very careful monitoring of rhythm is mandatory during the short- and long-term follow-up.